Persistence of earnings and prediction of future cash flows: the role of timely recognition of bad news - Kordestani, Gholamreza; Taqiporian, Maryam; Biglari, Vahid; Minaei, Vahid (Business: Theory and Practice, 2016)
Timely recognition of losses and expenses compared to revenues and increased values precipitates future expenses to match with current revenues. Thus, timely recognition of losses acts to reduce the persistence of earnings. However, it is expected that a more timely recognition of negative cash flows, as bad news, increase the power of earnings for predicting future cash flows. This study investigates the effects of the timely recognition of bad news (loss) versus the good news on the decrease of the persistence of earnings, and the effect of negative cash flows on forecasting future cash flows. In this study, two pooling type models and a panel type model have been used to estimate the persistence of earnings and cash flows. Seventy eight firms that were listed in the Tehran Stock Exchange during the period 2003–2010 were duly reviewed. The results of this research proved that the timely recognition of loss does not affect the persistence and the power of earnings for the purpose of forecasting future cash flows. The findings imply that conservatism does not distort persistence of earnings.